1999
DOI: 10.1097/00001888-199903000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of studentsʼ characteristics with their learning styles as they begin medical school

Abstract: The need to compete for grades in prerequisite courses may be a factor contributing to surface learning in new medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…Similar findings were obtained by Duff and Mc Kinstry [16]. A study conducted among medical novice students identified three main factors promoting a surface approach, which could lead to assessment-oriented learning: high workloads with tightly scheduled contact hours, predictability of assignments and assessment methods directed at recall of factual knowledge [28]. Ramsden further supports factors such as heavy workloads, poor feedback on student progress and activities promoting rote learning as elements encouraging learners to adopt a surface approach [29].…”
Section: Surface Approachsupporting
confidence: 64%
“…Similar findings were obtained by Duff and Mc Kinstry [16]. A study conducted among medical novice students identified three main factors promoting a surface approach, which could lead to assessment-oriented learning: high workloads with tightly scheduled contact hours, predictability of assignments and assessment methods directed at recall of factual knowledge [28]. Ramsden further supports factors such as heavy workloads, poor feedback on student progress and activities promoting rote learning as elements encouraging learners to adopt a surface approach [29].…”
Section: Surface Approachsupporting
confidence: 64%
“…Dramatic shift from multimodal to unimodal learning in postgraduate students was not well justified by the author but it was assumed that due to lack of time in clinical schedule and lack of didactic learning might be responsible for such type of shift. Need to compete for grade for undergraduate students unlike the postgraduate students might be the cause of such type of difference in unimodal leaning style as evidenced by the study done by Aaron in USA [37]. Unlike these reports the study done by whillier et al among 1st year to 5th year chiropractic students showed that neither multimodal style nor unimodal style varied in subsequent year.…”
Section: Learning Style and Level Of Medical Educationmentioning
confidence: 95%
“…Previous proposed constructs to explain low academic performance include study skills (e.g., Aaron, 1999), study habits (e.g., Murray, 2003), study attitudes (e.g., Zimmerman, 1977), study motivation (e.g., Melancon, 2002), meta-cognitive skills (e.g., Zeegers, 2001), study anxiety (e.g., Miller, 1972), procrastination (e.g. Pychyl, 2000) and depth of processing (e.g., Hall, 2001).…”
Section: Chronology Of the Study Of Study Habitsmentioning
confidence: 99%